Application of RUP (Rational Unified Process) Method in Optimizing Payment Systems and Processing Student Savings Data - Meri Mayang Sari; Po Abas Sunarya; Andri Cahyo Purnomo (CCIT Journal, 2023)
Humans continue to innovate in the field of technology, from these innovations it is expected to meet the needs of human life. In educational institutions the role of administration is very important to improve the education system for the better. One of them is in the educational institution of SMKN 5 Tangerang Regency, where the student administration payment system is not optimal. Because the system has not been integrated in the institution. Where the operator will enter and store data in different files, according to the student administration payments made, as well as in making reports. Guardians of students find it difficult to monitor and know when payments are due and the results of student administration payments. So that it has not been able to simplify and accelerate student services related to the information needed by guardians, and the performance of operators. The researcher uses the RUP (Rational Unified Process) development method and to analyze the problem the researcher uses PIECES (Performance, Information, Efficiency, Control, Economy, Service). The system is made using HTML, CSS, Java script, PHP and MySQL languages ​​as the database. The system modeling uses UML (Unified Modeling Language). The results obtained from the research is a payment system and student savings data processing. So that it can help in student services, make it easier to get information for guardians and also the performance of operators in making payments and processing student savings data, as well as in recapitulation and report generation.